IFN-Alpha-Mediated Differentiation of Dendritic Cells for Cancer Immunotherapy: Advances and Perspectives - Caterina Lapenta; Lucia Gabriele; Stefano Maria Santini (Vaccines, 2020)
The past decade has seen tremendous developments in novel cancer therapies through targeting immune-checkpoint molecules. However, since increasing the presentation of tumor antigens remains one of the major issues for eliciting a strong antitumor immune response, dendritic cells (DC) still hold a great potential for the development of cancer immunotherapy. A considerable body of evidence clearly demonstrates the importance of the interactions of type I IFN with the immune system for the generation of a durable antitumor response through its effects on DC. Actually, highly active DC can be rapidly generated from blood monocytes in vitro in the presence of IFN-α (IFN-DC), suitable for therapeutic vaccination of cancer patients. Here we review how type I IFN can promote the ex vivo differentiation of human DC and orientate DC functions towards the priming and expansion of protective antitumor immune responses. New epigenetic elements of control on activation of the type I IFN signal will be highlighted. We also review a few clinical trials exploiting IFN-DC in cancer vaccination and discuss how IFN-DC could be exploited for the design of effective strategies of cancer immunotherapy as a monotherapy or in combination with immune-checkpoint inhibitors or immunomodulatory drugs.